Postoperative Complications in Patients with Unrecognized Obesity Hypoventilation Syndrome Undergoing Elective Non-cardiac Surgery - Kaw, Roop (2015)
BACKGROUND: Among patients with obstructive sleep apnea (OSA) a higher number of medical morbidities are known to be associated with those that have obesity hypoventilation syndrome (OHS) compared to OSA alone. OHS can therefore pose a higher risk of postoperative complications after elective non-cardiac surgery (NCS) and is often unrecognized at the time of surgery. The objective of this study was to retrospectively identify patients with OHS and compare their postoperative outcomes with those who have OSA alone. METHODS: Patients meeting criteria for OHS were identified within a large cohort of patients with OSA who underwent elective NCS at a major tertiary care center. We identified postoperative outcomes associated with OSA and OHS as well as the clinical determinants of OHS (BMI, AHI). Multivariable logistic or linear regression models were used for dichotomous or continuous outcomes, respectively. RESULTS: Patients with hypercapnia from definite or possible OHS, and overlap syndrome are more likely to develop postoperative respiratory failure [OR: 10.9 (95% CI 3.7-32.3), p<0.0001], postoperative heart failure (p<0.0001), prolonged intubation [OR: 5.4 (95% CI 1.9-15.7), p=0.002), postoperative ICU transfer (OR: 3.8 (95% CI 1.7-8.6), p=0.002]; longer ICU (beta coefficient: 0.86; SE: 0.32, p=0.009) and hospital length of stay (beta coefficient: 2.94; SE: 0.87, p=0.0008) when compared to patients with OSA. Among the clinical determinants of OHS, neither BMI nor AHI showed associations with any postoperative outcomes in univariable or multivariable regression. CONCLUSIONS: Better emphasis is needed on preoperative recognition of hypercapnia among patients with OSA or overlap syndrome undergoing elective NCS